Distribution of Dimethylsulfoniopropionate Degradation Genes Reflects Strong Water Current Dependencies in the Sanriku Coastal Region in Japan: From Mesocosm to Field Study - Cui, Yingshun; Wong, Shu-Kuan; Kaneko, Ryo; Mouri, Ayako; Tada, Yuya; Nagao, Ippei; Chun, Seong-Jun; Lee, Hyung-Gwan; Ahn, Chi-Yong; Oh, Hee-Mock; Sato-Takabe, Yuki; Suzuki, Koji; et al. (Frontiers in Microbiology, 2020)
Dimethyl sulphide (DMS) is an important component of the global sulphur cycle as it is the most abundant sulphur compound that is emitted via the ocean surface to the atmosphere. Dimethylsulfoniopropionate (DMSP), the precursor of DMS, is mainly produced by phytoplankton and is degraded by marine bacteria. To reveal the role of bacteria in the regulation of DMSP degradation and DMS production, mesocosm and field studies were performed in the Sanriku Coast on the Pacific Ocean in northeast Japan. The responsible bacteria for the transformation of DMSP to DMS and the assimilation of DMSP were monitored and the genes encoding DMSP lyase (dddD and dddP) and DMSP demethylase (dmdA) were analysed. The mesocosm study showed that the dmdA subclade D was the dominant DMSP degradation gene in the free-living (FL) and particle-associated (PA) fractions. The dddD gene was found in higher abundance than the dddP gene in all the tested samples. Most importantly, DMS concentration was positively correlated with the abundance of the dddD gene. These results indicated that bacteria possessing dmdA and dddD genes were the major contributors to the DMSP degradation and DMS production, respectively. The genes dmdA subclade D and dddP were abundant in the Tsugaru Warm (TW) Current, while the dmdA subclade C/2 and dddD genes were dominant in the Oyashio (OY) Current. Functional gene network analysis also showed that the DMSP degradation genes were divided into OY and TW Current-related modules and genes sharing similar functions were clustered in the same module. Our data suggest that environmental fluctuations resulted in habitat filtering and niche partitioning of bacteria possessing DMSP degradation genes. Overall, our findings provide novel insights into the distribution and abundance of DMSP degradation genes in a coastal region with different water current systems.